2018
DOI: 10.1021/acsnano.8b04931
|View full text |Cite
|
Sign up to set email alerts
|

A Dual-Band Multilayer InSe Self-Powered Photodetector with High Performance Induced by Surface Plasmon Resonance and Asymmetric Schottky Junction

Abstract: A dual-band self-powered photodetector (SPPD) with high sensitivity is realized by a facile combination of InSe Schottky diode and Au plasmonic nanoparticle (NP) arrays. Comparing with pristine InSe devices, InSe/Au photodetectors possess an additional capability of photodetection in visible to near-infrared (NIR) region. This intriguing phenomenon is attributed to the wavelength selective enhancement of pristine responsivities by hybridized quadrupole plasmons resonance of Au NPs. It is worth pointing out tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
207
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(215 citation statements)
references
References 55 publications
8
207
0
Order By: Relevance
“…g) Schematic diagram of the device structure of InSe/Au SPPD. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: D Material‐based Schottky Junction Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…g) Schematic diagram of the device structure of InSe/Au SPPD. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: D Material‐based Schottky Junction Photodetectorsmentioning
confidence: 99%
“…Although asymmetric Schottky junction photodetectors enable self‐powered light detection without relying on external power supplies, the small photoresponse current of the Schottky junction self‐powered photodetector limits real‐life applications. Therefore, Dai et al fabricated a self‐powered photodetector with high sensitivity and high response performance by loading an Au plasma nanoparticle array on the surface of the InSe Schottky diode (Figure g). Compared to the original InSe Schottky junction photodetector, the InSe Schottky junction photodetector has higher sensitivity and photoresponse performance and has additional photodetection capability in the visible to near‐infrared region.…”
Section: D Material‐based Schottky Junction Photodetectorsmentioning
confidence: 99%
“…The simulated optical field distribution confirmed that plasmon resonance effect mainly originated from the near‐field oscillation and scattering effect. Tian et al demonstrate their graphene photodetectors enhanced by plasmonic Cu 3 − x P colloidal nanocrystals with an ultrahigh responsivity (1.59 × 10 5 A/W) . Dai et al fabricated a dual band self‐powered photodetector by a combination of InSe Schottky diode and Au plasmonic nanoparticle arrays as shown in Figure C .…”
Section: Recent Design Strategies For 2d‐based Photodetectorsmentioning
confidence: 99%
“…d) Schematic illustration of self‐powered, plasmon‐induced dual band photodetector. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Mechanism Of Plasmonic‐assisted Devicesmentioning
confidence: 99%
“…Furthermore, the proposed structure qualifies to the plasmonic device to extend its photoresponse range by four orders of magnitude. Dai et al used the plasmonic technique to develop 2D material InSe‐based photodetector with an asymmetric geometry, as shown in Figure d . The proposed heterostructure exhibits the excellent responsively of 369 mA W −1 at light intensity of 365 nm, on/off ratio of 10 3 , and exhibits self‐powered photodetector.…”
Section: Mechanism Of Plasmonic‐assisted Devicesmentioning
confidence: 99%